The Effect of Ag and Ge Multi-micro Alloying Elements on Micro-structure and Mechanical Properties of Al-(3.2) Cu-(2) Li-(0.6) Mg Alloys - Enass Laith Ali; Abdalwahid K Rajih (Current Approaches in Engineering Research and Technology Vol. 4, 2024)
The present study attempts to investigate the possible improvement of replacing (Cu) with (Li) in (Al-Cu) alloys used in aerospace industries. Space industries always require lightweight materials, high strength, fatigue, corrosion, and thermal stability. Aluminum alloys, for example, Al-Cu-Mg and Al-Zn-Mg, have good mechanical properties in addition to their low density. It is commonly known that the superior characteristics of (Al-Li) alloys over congenital (Al) alloys make them desirable for usage in aerospace and the military. Since (Li) decreased the plane’s weight, it is possible to reach higher speeds. Intruded strength and hardness are two more enhancements. Alloys were prepared during this work by casting, they include (Al-Li-Cu-Mg-Zr), (Al-Li-Cu-Mg-Zr-Ag), and (Al-Li-Cu-Mg-Zr-Ag-Ge) alloys. Results showed that the addition of 0.35%Ag to Al-Li-Cu-Mg-Zr alloy improves strength from (42MPa) to (127MPa) when aging at 175°C. improve hardness from (156.64 Hv) to (173.74Hv) at the same temperature aging. But the deterioration when the addition of 0.2 Ge at Al-Li-Cu-Mg-Zr alloy weakness strength from (127MPa) to (26MPa) at the same time improved hardness from (156.64Hv) to (171.76Hv) at the same temperature. The C alloy found that the tensile strength decreased to (26 MPa) the reason for the presence of germanium, which works on the expansion but found when added to the aluminum alloy - Lithium increases the lithium’s ability in aluminum, so it inhibits the phase deposition (Ge4Zr5), (Al3Li) as long as in the rigid solution either After the process of aging, it is deposited in the form of rods that are almost identical, not cutable by the moving masses, thus reducing tensile strength. Optical microscopy (OM), and X-ray diffraction (XRD) were done to study the structure and the surface features and chemical composition of the alloys. Numerous phases are displayed, including (Al3Li), (Al3Zr), (Al2MgLi), omega (\(Ω\)) precipitates, (Ag2CuLi), and (Ge4Zr5), which all have an impact on the mechanical and chemical properties. The pin-on-disc testing method was frequently employed to look at sliding wear. B notable improvement in the alloy’s resistance to wear. Just 60% less weight was lost than with the other alloys.